BURDEN OF PROVING WORK ABSENCE IN OVERTIME WAGE CLAIMS - Nadaek, Nason; Hambali, Ahmad; Murti, Ria Trisno (International Peneliti Ekonomi, Sosial dan Teknologi, 2026)
Overtime pay demands occur when a company employs its workers to work overtime, but the workers are not given overtime pay, so that the workers are forced to make a report or complaint to the labor inspector, to be examined as a basis for making calculations and determinations, because overtime pay is a right guaranteed by Article 78 paragraph (2) of Law No. 6 of 2023. In practice, overtime pay claims are very difficult to obtain, because labor inspectors who handle complaints always place the burden of proof on the workers who file complaints or demands. The main evidentiary document that must be proven in overtime pay claims is work attendance. Considering that work attendance only exists within the company, the burden of proof placed by labor inspectors on workers is the wrong burden of proof, because how can a party who does not have evidence be burdened to prove it.